Generating Synthetic Magnetic Resonance Images for Deep Learning Applications with Limited Labeled Data - Felipe, Caio dos S.; Schiavon, Dieine E. B.; Alva, Thatiane A. P.; Becker, Carla D. L. (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2025)
This study addresses medical imaging data scarcity in AI development by using Progressive Growing of GANs (PGGAN) and transfer learning (TL) to generate synthetic MRIs of frontotemporal dementia variants. Our pre-trained foundation model achieved high anatomical fidelity (FID: 21.6008), while TL significantly improved image quality compared to models trained from scratch, reducing FID scores from ~115 to ~40. Although clinical validation is still needed, this framework offers a promising approach to expand limited medical datasets while maintaining anatomical accuracy for rare disease analysis.